Validating effectiveness of safety requirements' compliance evaluation in process assessments. Issue 3 (9th July 2019) - Varkoi, Timo; Mäkinen, Timo; Cameron, Frank; Nevalainen, Risto
Abstract: Safety is the primary concern when developing systems containing software in the nuclear power domain. Process assessments are used to ensure quality of the development processes for safety‐critical systems. Regulators of the nuclear power industry have increased requirements concerning the systems development processes. Now, process assessments are integrated in the qualification of the systems and are expected to provide information not only based on the assessment model but also about the domain‐specific requirements. Therefore, a specific activity, compliance evaluation, was inserted into the assessment process to provide detailed information that supports analysis of the compliance to the domain standards. Compliance evaluation utilizes assessment findings to create evidence of the relevant domain‐specific requirements. The main purpose of this study is to validate effectiveness of compliance evaluation by analyzing assessment findings and their relation to the requirements of a safety‐critical domain. The analysis is based on representing the data in compliance evaluation reports as binary relations. The results of this analysis indicate that process assessment findings are also relevant when evaluating compliance to other sets of requirements. The results can significantly support the trustworthiness of the process assessment method and ensure effective use of process assessments. Abstract : Nuclear SPICE is used to assess development processes of safety‐related systems in the nuclear power industry. We used the results of three assessments to determine whether the connections between the processes and domain‐specific requirements (DSRs) could efficiently provide evidence for compliance evaluation. We found that many of the DSRs were consistently connected to specific Nuclear SPICE processes. The results are encouraging and confirm that process assessments produce efficiently useful information for safety qualification of systems.